ANALYSIS OF THE VALIDITY OF CYBER NOTARY-BASED NOTARY DEEDS IN THE PERSPECTIVE OF CIVIL LAW - Aksa, Febi Sabrina; Ginting, Lilawati (International Journal of Cultural and Social Science, 2026)
The development of technology and information has brought significant changes in various aspects of life, including in the practice of the legal profession in Indonesia. This research is motivated by the development of the transformation of the notary world towards the digital era through the concept of cyber notary. Cyber notary is the notary's authority to certify transactions electronically. Although Article 15 paragraph (3) of Law Number 2 of 2014 concerning the Notary Position (UUJN) provides the opportunity for such authority, there is a discrepancy with Article 16 paragraph (1) letter m of the UUJN which requires the physical presence of the parties and the direct reading of the deed. This research is a type of normative legal research with a statute approach that is descriptive and analytical. The results of the study show that regulations regarding cyber notaries in Indonesia are still experiencing juridical insynchronization and ambiguity of meaning because the term is only included in the explanation section without a clear operational definition. From a civil law perspective, deeds made by the cyber notary method currently do not have the same legal certainty as conventional authentic deeds because the formality requirement of "physical presence" in Article 1868 of the Civil Code has not been met. The implication is that the deed risks degrading the power of proof into a deed under hand and losing its executory nature. Therefore, synchronization between the UUJN, THE ITE Law, and the Civil Code is needed as well as clear technical regulations to ensure legal certainty for practitioners and the public.